2009
DOI: 10.1158/1055-9965.epi-08-0496
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Retinol and Prognosis of Postmenopausal Breast Cancer Patients

Abstract: Background: The role of retinol (vitamin A) in breast cancer prognosis has never been investigated in postmenopausal women. We prospectively assessed the long-term prognostic role of retinol plasma levels in a cohort of postmenopausal breast cancer patients. Patients and Methods: We investigated 208 women selfreported as postmenopausal operated on for T 1-2 N 0 M 0 breast cancer who participated in a chemoprevention trial as controls and never received chemotherapy or hormone therapy. Plasma samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
1
14
2
2
Order By: Relevance
“…Published data, which have shown age aspects of content retinol in women are ambiguous also [13,30,31]. Some studies have shown association between low plasma retinol level and different pathology such as breast cancer [32], stroke [33] in Table 3 Correlation between antioxidant system parameters in reproductive, perimenopausal, and postmenopausal women.…”
Section: Parametersmentioning
confidence: 99%
“…Published data, which have shown age aspects of content retinol in women are ambiguous also [13,30,31]. Some studies have shown association between low plasma retinol level and different pathology such as breast cancer [32], stroke [33] in Table 3 Correlation between antioxidant system parameters in reproductive, perimenopausal, and postmenopausal women.…”
Section: Parametersmentioning
confidence: 99%
“…Plasma concentrations of ROH reach 2-3 μM in humans [2,39]. Therefore, the concentrations used in the present study are physiological relevant.…”
Section: Discussionmentioning
confidence: 88%
“…ROH is metabolized in cells to retinal and then to all-trans retinoic acid [1], which, in turn, may be isomerized to 9-cis retinoic acid (9-cis RA) or 13-cis retinoic acid . Plasma ROH levels are inversely correlated with the breast cancer survival in postmenopausal women [2], and the incidence of breast cancer is inversely correlated with total ROH consumption [3][4][5]. Plasma ROH or carotenoid levels are also inversely associated with the risk of ovarian [6], bladder [7], lung and other cancers [8].…”
Section: Introductionmentioning
confidence: 99%
“…Deux études de cohorte récentes confi rmeraient cette hypothèse. Les taux initiaux de rétinol plasmatique dans une étude prospective chez 208 Italiennes ménopausées [34] T1-2N0M0 font apparaître une survie moindre chez les femmes avec un taux inférieur à la médiane (< 2,08 µmol/l) mais de manière signifi cative uniquement chez les femmes âgées de plus de 55 ans. De même, dans l'essai randomisé WHEL [66], l'analyse des caroténoïdes plasmatiques des 1 551 femmes du bras témoin montre que, par rapport aux femmes du quartile le plus bas (1,04 µmol/l), celles dont les taux sont les plus élevés (4,19 µmol/l) ont un risque de rechutes réduit (0,57 [IC 95 % : [0,37-0,88]).…”
Section: Rétinoïdes (Niveaux 2-3)unclassified